A gene regulatory network for antenna size control in carbon dioxide-deprived Chlamydomonas reinhardtii cells. Issue 4 (27th January 2021) - Blifernez-Klassen, Olga; Berger, Hanna; Mittmann, Birgit Gerlinde Katharina; Klassen, Viktor; Schelletter, Louise; Buchholz, Tatjana; Baier, Thomas; Soleimani, Maryna; Wobbe, Lutz; Kruse, Olaf
Abstract: In green microalgae, prolonged exposure to inorganic carbon depletion requires long-term acclimation responses, involving modulated gene expression and the adjustment of photosynthetic activity to the prevailing supply of carbon dioxide. Here, we describe a microalgal regulatory cycle that adjusts the light-harvesting capacity at photosystem II (PSII) to the prevailing supply of carbon dioxide in Chlamydomonas ( Chlamydomonas reinhardtii ). It engages low carbon dioxide response factor (LCRF), a member of the squamosa promoter-binding protein (SBP) family of transcription factors, and the previously characterized cytosolic translation repressor nucleic acid-binding protein 1 (NAB1). LCRF combines a DNA-binding SBP domain with a conserved domain for protein–protein interaction. LCRF transcription is rapidly induced by carbon dioxide depletion. LCRF activates NAB1 transcription by specifically binding to tetranucleotide motifs present in its promoter. Accumulation of the NAB1 protein enhances translational repression of its prime target mRNA, encoding the PSII-associated major light-harvesting protein LHCBM6. The resulting truncation of the PSII antenna size helps maintaining a low excitation during carbon dioxide limitation. Analyses of low carbon dioxide acclimation in nuclear insertion mutants devoid of a functional LCRF gene confirm the essentiality of this novel transcription factor for the regulatory circuit. Abstract : The transcription factor low carbon dioxide response factor activates the transcription of the translational repressor nucleic acid-binding protein 1 (NAB1) by binding to the NAB1 promoter, a process required for antenna size adjustment following CO2 limitation in Chlamydomonas .